Gender and law in the Hebrew Bible and the ancient Near East - Matthews, Victor Harold; Levinson, Bernard M. (Bernard Malcolm); Frymer-Kensky, Tikva Simone (Journal for the study of the Old Testament. Supplement series ;, 1998)
This striking new contribution to gender studies demonstrates the essential role of Israelite and Near East law in the historical analysis of gender. The theme of these studies of Babylonian, Hittite, Assyrian, and Israelite law is this: What is the significance of gender in the formulation of ancient law and custom? Feminist scholarship is enriched by these studies in family history and the status of women in antiquity. At the same time, conventional legal history is repositioned, as new and classical texts are interpreted from the vantage point of feminist theory and social history. Papers f.